State-of-Art in Innate Immunity - Fischer, Silvia; Deindl, Elisabeth (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The innate immune system is the first line of defense against bacterial and viral infections and sterile inflammation through the recognition of pathogen-associated molecular patterns (PAMPs) by pathogen recognition receptors (PRRs) resulting in the production of proinflammatory and antiviral cytokines and chemokines. Several damage-associated molecular patterns (DAMPs), which were released by passive or active mechanisms under sterile conditions, are additionally recognized by PRRs and can cause or even aggravate the inflammatory response. In this special issue many aspects of innate immunity are summarized. Mechanisms of different DAMPs to induce pro- and anti-inflammatory activities, functions of different immune cells, as well as the crosstalk between coagulation and innate immunity were described. Furthermore, aspects of autoinflammatory diseases, types of programmed cell death pathways, and insect immunity are covered. Finally, therapeutic options for the treatment of diseases related to autoimmunity or infections are suggested. Overall, this special issue presents a broad overview of activities related to sterile inflammation and defense mechanisms of innate immunity.